Determinants of capital structure of food industry in Malaysia / Nina Baizurah Md Som - Md Som, Nina Baizurah (Faculty of Business Management, 2017)
This paper involve in finding the determination of capital structure of food industry in Malaysia. The findings found in previous studies cannot represent overall determinants of Malaysia firms’ capital structure because different sector have different firm characteristics. Therefore, this research can create new knowledge on food producer sector firm capital structure determinants and fulfill the existing gap. It is include two types of variables. First is dependent variable which involved capital structure and measured by using debt ratio. Second is independent variables which are involve return on equity (ROE), return on assets (ROA), liquidity, profitability, size of firm and growth opportunity. As sample of this research it is include 64 observations during the period 2008 until 2015. It is also involve 8 firms that involved in food industry in Malaysia and listed in the Bursa Malaysia. It is used three model regression whish are Pooled OLS, Fixed Effect Model and Random Effect Model. A software package named STATA will be used in order to get the finding answers in analyzing the related data. Several test will be involve in this observation such as F-statistic, Brauch and Pagan Lagrangian Multiplier test and Hausman test.